2020
DOI: 10.1371/journal.pbio.3000722
|View full text |Cite
|
Sign up to set email alerts
|

NCX1 represents an ionic Na+ sensing mechanism in macrophages

Abstract: Inflammation and infection can trigger local tissue Na + accumulation. This Na +-rich environment boosts proinflammatory activation of monocyte/macrophage-like cells (MΦs) and their antimicrobial activity. Enhanced Na +-driven MΦ function requires the osmoprotective transcription factor nuclear factor of activated T cells 5 (NFAT5), which augments nitric oxide (NO) production and contributes to increased autophagy. However, the mechanism of Na + sensing in MΦs remained unclear. High extracellular Na + levels (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 66 publications
(91 reference statements)
4
39
0
Order By: Relevance
“…Jantsch et al provided direct and firm evidence that increased concentrations of Na + in the tissue following a high-salt diet improved control of L. major in vivo via NFAT5-dependent induction of NOS2 [154] . The Na + /Ca 2+ exchanger 1 (NCX1, also known as solute carrier family 8 member A1 [SLC8A1]) accounted for the Na + influx during exposure of macrophages to high salt conditions [155] . Recent data indicate that the effect of tissue osmolarity on phagocyte functions might not be restricted to classically activated (M1) macrophages, but could also pertain to alternatively activated (M2) macrophages [156] .…”
Section: Macrophages As Antileishmanial Effector Cells In Leishmaniasmentioning
confidence: 99%
“…Jantsch et al provided direct and firm evidence that increased concentrations of Na + in the tissue following a high-salt diet improved control of L. major in vivo via NFAT5-dependent induction of NOS2 [154] . The Na + /Ca 2+ exchanger 1 (NCX1, also known as solute carrier family 8 member A1 [SLC8A1]) accounted for the Na + influx during exposure of macrophages to high salt conditions [155] . Recent data indicate that the effect of tissue osmolarity on phagocyte functions might not be restricted to classically activated (M1) macrophages, but could also pertain to alternatively activated (M2) macrophages [156] .…”
Section: Macrophages As Antileishmanial Effector Cells In Leishmaniasmentioning
confidence: 99%
“…NCX is also engaged in insulin secretion, calcium reabsorption in the kidney, and learning and memory related to the hippocampus. 151,154 We will not elaborate on it here.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to epithelial cells, immune cells lack an apical-basal axis orientation, indicating that their ability to handle changes in the local ionic composition will differ from the mechanisms in epithelial cells. In addition, in macrophages for instance, the resting membrane potential is not as negative as in epithelial cells [58,59], which has implications on the activity and thermodynamics of channels, exchangers, and transporters. Our group reported that the Na + /Ca 2+ exchanger plays an important role in the detection of increases in local extracellular sodium levels and contributes to amplifying proinflammatory mouse macrophage responses [58].…”
Section: Trends In Immunologymentioning
confidence: 99%
“…In addition, in macrophages for instance, the resting membrane potential is not as negative as in epithelial cells [58,59], which has implications on the activity and thermodynamics of channels, exchangers, and transporters. Our group reported that the Na + /Ca 2+ exchanger plays an important role in the detection of increases in local extracellular sodium levels and contributes to amplifying proinflammatory mouse macrophage responses [58]. However, sodium handling ensuing cellular responses remain undetermined and we do not know how other immune cells might detect and/or handle excess sodium amounts.…”
Section: Trends In Immunologymentioning
confidence: 99%
See 1 more Smart Citation